Electrical energy storage systems in electricity generation: Energy policies, innovative technologies, and regulatory regimes. (April 2016) - Kyriakopoulos, Grigorios L.; Arabatzis, Garyfallos
Abstract: Electricity plays a dominant role to the citizens׳ well-being and the social prosperity of the developed economies. Electricity perspectives have attracted the research interest of the scientific community during the last two decades due to its determining impact upon transportation modes (electric-based mobility: electric vehicles–EVs, hybrid cars, and electric drive-trains), energy-consumed household tasks (Smart House and Smart Grid concepts), working environment, and leisure activities. Electricity generation is mainly determined by the following features: on-grid (mainland) and off-grid (including exploitation of renewables in remote areas) production, peak (during the day) and off-peak (during the night) daytimes of energy production and consumption, efficient and reliable power supply, capability and reliability of energy storage technologies, energy market potential in the future. This study further explores the following issues: which technologies will be most needed, in which technologies there is room for further development, which policy considerations will influence rollout and penetration, and what implementation problems may be expected. Finally, this study addresses a wide spectrum of energy policies regarding the electrochemical, mechanical, and thermal energy storage technologies. In parallel, the study discussed global regulatory regimes of the post-2015 development agenda of Rio20+ United Nations Conference on Sustainable Development that should be adapted to electricity generation under the political initiatives of "Sustainable Development Goals" (SDGs) and "Millennium Development Goals" (MDGs). Finally, the key-issues of research, operation, applicability, and pricing trend of energy storage technologies are addressed while the future orientations of these technologies are outlined.